Semi-inverse Monte Carlo reconstruction of two-phase heterogeneous material using two-point functions. (11th November 2009) - Garmestani, H.; Baniassadi, M.; Li, D.S.; Fathi, M.; , S. Ahzi
A new Monte Carlo (MC) methodology using ant Colony and kinetic growth models is developed to reconstruct the microstructure of two-phase composites using correlation statistics. After the initial patterns are generated, the new patterns evolved by introducing optimisation parameters for rotation, shrinkage, transportation and distribution. The realisations are then optimised using kinetic growth rate applied to each representative cell. For each realisation, the final microstructures are then compared to the experimental results through minimisation of the error function. Finally an optimisation methodology was developed to introduce initial input parameters for MC simulation to minimise the error function.